Signaling networks in human hepatocarcinogenesis: novel aspects and therapeutic options - Breuhahn, Kai; Schirmacher, Peter (Progress in molecular biology and translational science, 2010)
Hepatocellular carcinoma (HCC) represents one of the most common human malignancies with poor prognosis. Because therapeutic strategies are insufficient for most HCC patients, there is a great need to determine the central molecular mechanisms and pathways in order to derive novel targets for systemic therapy. There is vast evidence that not only the dysregulation of distinct signaling cascades, but also their interactions at different levels, affect tumor cell function. Through these interactions, the effects of pathways can be increased, and even new tumor-supporting qualities acquired that further facilitate HCC progression. Although several approaches for the modulation of these relevant pathways are under development, future therapeutic strategies should take into account that oncogenic stimuli cannot be understood in a monodimensional manner. In order to avoid escape mechanisms during therapy, strategies based on comprehensive knowledge of the interactive regulatory network in hepatocarcinogenesis are necessary.
Gesehen am 01.03.2023